PELATIHAN TERAPI EMOTIONAL FREEDOM TECHNIQUE DENGAN AFIRMASI BERBASIS BUDAYA PADA GURU BK SEKOLAH DI KABUPATEN LAMONGAN - Endang Pudjiastuti Sartinah; Budi Purwoko; Budiyanto Budiyanto (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
This Community Service aims to increase the competence of counseling teachers or counselors in applying the Emotional Freedom Technique (EFT) by providing theoretical and practical material for mastering EFT procedures. Theoretical material includes the basic concepts of therapy, therapeutic goals, therapeutic procedures, therapist and client relationships, therapeutic techniques, and indicators of therapeutic success. Community Service is carried out through guided training and facilitating trials of the application of EFT therapy to school counselors. Activity partners include 40 counselors representing the junior high, high school, and vocational schools in the Lamongan district, East Java. The pre-test and post-test results showed an increase from the pre-test average score of 49 to the post-test average score of 62.